EVALUATION OF THE IMPLEMENTATION OF INTEGRATED THEMATIC LEARNING IN ISLAMIC RELIGIOUS EDUCATION - Masrifa Hidayani (CV. ADIBA AISHA AMIRA, 2024)
Integrating the concept of integrated thematic learning into Islamic religious learning has great potential to improve the quality of students' educational process. This approach allows the cultivation of religious values that are connected to various other scientific aspects in a thematic series, thus facilitating multidimensional and contextual understanding for students. The results of the literature review conclude that the development of theme-based learning across studies has great potential to increase the effectiveness of student learning, where religious teachings can be channeled along with other subject matter so as to form a comprehensive and meaningful understanding for them. However, the implementation of the concept of integrated thematic learning in the fourth grade of Islamic religion is still faced with various obstacles, such as the lack of teacher understanding of this concept, the lack of training and mentoring, and the limited learning resources and supporting facilities. Educators often find it difficult to plan and implement cross-curricular learning properly. On the other hand, several key enablers of this development can enhance its success, including the support of the principal, the availability of appropriate teaching materials, parent and community participation, and collaboration among teachers. This study concludes that to improve the effectiveness of integrated thematic learning in Islamic religious education, there needs to be more focus from schools and the government on providing training and mentoring to educators. In addition, it is also necessary to increase the availability and quality of learning facilities. These steps are expected to implement theme-based learning more effectively to support students' character development and academic achievement.